2020
DOI: 10.1182/blood-2020-134774
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Single-Agent Inotuzumab Ozogamicin in Pediatric CD22-Positive Relapsed/Refractory Acute Lymphoblastic Leukemia: Results of the ITCC-059 Study

Abstract: Background: Inotuzumab ozogamicin (InO) was well tolerated and demonstrated anti-leukemia activity in heavily pre-treated pediatric patients (pts) with CD22-positive relapsed/refractory (R/R) acute lymphoblastic leukemia (ALL) in the Phase (Ph) I ITCC-059 study. With the established recommended phase 2 dose (RP2D) (1.8 mg/m2/course, as in adults) a consecutive Ph II study has been performed, sponsored by Erasmus MC and supported by Pfizer (NTR57360). Study design: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A phase I/II study is currently ongoing in children with R/R BCP ALL (study European Innovative Therapies for Children with Cancer [ITCC]-059) within the ITCC group. The phase I study established the recommended phase II dose (RP2D) at 1.8 mg/m 2 , similar as in adults, with an ORR of 80%, which was confirmed in the phase II part of the study [38,39]. An additional phase 1b cohort is ongoing to test the combination of InO with a modified R3 reinduction regimen.…”
Section: Antibodyedrug Conjugates 231 Inotuzumab Ozogamicinmentioning
confidence: 80%
See 1 more Smart Citation
“…A phase I/II study is currently ongoing in children with R/R BCP ALL (study European Innovative Therapies for Children with Cancer [ITCC]-059) within the ITCC group. The phase I study established the recommended phase II dose (RP2D) at 1.8 mg/m 2 , similar as in adults, with an ORR of 80%, which was confirmed in the phase II part of the study [38,39]. An additional phase 1b cohort is ongoing to test the combination of InO with a modified R3 reinduction regimen.…”
Section: Antibodyedrug Conjugates 231 Inotuzumab Ozogamicinmentioning
confidence: 80%
“…A particular concern with the use of InO is sinusoidal obstruction syndrome, likely owing to the calicheamicin component. Warnings were raised by studies in adults, showing a relatively high incidence in the transplant population (30% of transplanted patients after InO), similar to gemtuzumab ozogamicin (GO) [36,37,39]. Current recommendations, as per the summary of product characteristics, are to limit InO to 2e3 cycles if a patient is a candidate for HSCT and to use non-alkylating chemotherapy.…”
Section: Antibodyedrug Conjugates 231 Inotuzumab Ozogamicinmentioning
confidence: 99%
“…The recent phase 2 ITCC-059 study has also demonstrated the efficacy of IO in 32 heavily pre-treated R/R paediatric and adolescent patients aged one to 17 years. Of the 28 treated patients, there was an ORR of 81.5%, including 95% achieving MRD negativity in those that responded, and 55% of patients were alive at one year [ 79 ]. Four cases of VOD/sinusoidal obstruction syndrome (SOS) were reported, including three of nine transplanted patients [ 79 ].…”
Section: Targeting the “B” In B-allmentioning
confidence: 99%
“…Of the 28 treated patients, there was an ORR of 81.5%, including 95% achieving MRD negativity in those that responded, and 55% of patients were alive at one year [ 79 ]. Four cases of VOD/sinusoidal obstruction syndrome (SOS) were reported, including three of nine transplanted patients [ 79 ].…”
Section: Targeting the “B” In B-allmentioning
confidence: 99%